Mycorrhiza stimulates Rhizobium infection in Paraserianthes falcataria (L.) I.C. Nielson under Hg contamination - Irma Latifah; Idris Idris; Toga Pangihotan Napitupulu; Azra Zahra Nadirah Ikhwani; Gunawan Ruhiyat; I Nyoman Sumerta; Atit Kanti; Fitri Yola Amandita; I Made Sudiana (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2021)
Symbiosis of and AMF increase soybean production, but the information on the association between these microbes in Paraserianthes falcataria (L.) I.C. Nielson or ‘sengon’ under Hg contamination is limited. We observed P. falcataria inoculated with arbuscular mycorrhiza fungi (Glomus sp.) stimulate nodule formation under Hg contamination. The study was set up in a pot experiment in the growth chamber a the Hg concentration was adjusted to 50 ppm in soil medium. Inoculation of AMF stimulates nodule formation and increases P. falcataria tolerance to Hg. We isolated several bacteria from the rhizosphere belonging to Rhizobium group and others. Understanding the ecology of soil bacteria is important for Hg bioremediation using P. falcataria.